2019
DOI: 10.18632/oncotarget.26544
|View full text |Cite
|
Sign up to set email alerts
|

Photo-immune therapy with liposomally formulated phospholipid-conjugated indocyanine green induces specific antitumor responses with heat shock protein-70 expression in a glioblastoma model

Abstract: Glioblastoma (GBM) is the most common malignant brain tumor, and infiltrates into the surrounding normal brain tissue. Induction of a tumor-specific immune response is one of the best methods to obtain tumor-specific cytotoxicity. Photodynamic therapy (PDT) is known to effectively induce an antitumor immune response. We have developed a clinically translatable nanoparticle, liposomally formulated phospholipid-conjugated indocyanine green (LP-iDOPE), applicable for PDT. This nanoparticle accumulates in tumor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…It is proposed that continuous treatment is required for long-term remission. It was recently reported that the antitumour effect of the PHT/ICG-Lipo combination therapy was associated with an immunological mechanism (20). According to a report into using immunotherapy with programmed death (PD)-ligand 1 to treat a tumour, the tumour size temporarily increased and subsequently decreased (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that continuous treatment is required for long-term remission. It was recently reported that the antitumour effect of the PHT/ICG-Lipo combination therapy was associated with an immunological mechanism (20). According to a report into using immunotherapy with programmed death (PD)-ligand 1 to treat a tumour, the tumour size temporarily increased and subsequently decreased (21).…”
Section: Discussionmentioning
confidence: 99%
“…Activated CD8 + T cells actively surveil the body for neoplastic cells and induce apoptosis whenever tumor cells are encountered, thereby providing longterm tumor control. Therefore, ICD induced by PDT has the potential to stimulate immune activation and surveillance, contributing to long term tumor control is observed in preclinical models (63,(66)(67)(68)(69).…”
Section: Emerging Technologies Advancements In Pdt For Glioblastomasmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a therapeutic approach involving the administration of a photosensitizer which upon the application of light, produces cytotoxic levels of ROS and triggers antitumor immune responses [148,231]. Most of the photosensitizers such as protoporphyrin IX (PpIX), 5,10,15,20tetrakis(3-hydroxyphenyl) chlorin (mTHPC) and photofrin are excited with visible spectrum light which lacks the penetrating properties of NIR light [148,232,233].…”
Section: Combined Photodynamic/pttmentioning
confidence: 99%
“…UCNP have been utilized for PTT and PDT of GBM after NIR irradiation exhibiting pronounced antitumor effects in vitro and in vivo [206,235]. Moreover, some researchers have utilized indocyanine (ICG) conjugated liposomal and silk fibroin nanoparticles that do not possess any light emitting properties coupled with NIR spectrum light and have reported substantial PDT/PTT effects in rodent GBM models without the use of UCNP or visible light application [221,231].…”
Section: Combined Photodynamic/pttmentioning
confidence: 99%